Improving Arabic Language Speaking Skills Through Students' Muhadatsah in Special Programs in Madrasah - Kusuma Wardani, Amallia Putri; Latifatul Inayati, Nurul (Institut Agama Islam An-Nawawi Purworejo, 2025)
This research aims to describe the improvement of Arabic speaking skills through the Muhadatsah method in Special Program (PK) students at Madrasas, especially in class VII students at MTs Negeri 2 Sukoharjo in the 2024/2025 academic year. Arabic, which is the main language of learning at Madrasas, has an important role in daily communication, worship, and reading the Koran. Learning Arabic through Muhadatsah aims to enable students to communicate fluently in Arabic, learn more about worship, and make it easier to read the Koran and pray. The research method used is a qualitative method with a qualitative descriptive approach. Data collection techniques were carried out through observation, interviews and documentation, while data validity testing used triangulation. Data analysis was carried out in the following steps: 1) data collection, 2) data reduction, 3) data presentation, 4) drawing conclusions, and 5) verification. The research results showed that the Arabic speaking skills of class VII PK MTs Negeri 2 Sukoharjo students improved through Muhadatsah learning which involved making daily conversations, making speeches, singing, and watching Arabic videos. However, there are several obstacles, such as a lack of basic Arabic for some students and teachers' difficulty in managing time. The proposed solution is to provide assignments at school and at home, so that students can participate in learning better. The impact of this research can enrich Islamic education scholarship, especially in teaching Muhadatsah as an integral part of Arabic language learning. This approach can strengthen students' Arabic language communication skills which are important for daily worship activities, as well as exploring Islamic religious knowledge in more depth.